Socialism and Foreign Policy - Miller, Kenneth E. author. aut Link
VIII, 301 p.
Keywords: This book is intended as a contribution to the study of the relation of political ideas and governmental policies. It seeks to examine and evaluate the British Labour Party's early efforts to apply socialist theories to foreign policy actions. Since I have focused on these ideas and events, I have not attempted to take into account happenings on the British domestic front that, though important to the Labour Party and the trade unions, did not directly affect foreign policy. Nor are matters of imperial or Commonwealth policy considered, except as they relate to the development of socialist theories and interpretations or as they influenced Great Britain's relations with other independent states. I must express my appreciation for their assistance to Drs. Malcolm Moos, Thomas 1. Cook, and Carl B. "Swisher, under whose direction this project first began at the Johns Hopkins University; to Mrs. E. Rickman of the Labour Party's Library and to Mrs. Gladys D. Cremer of the Fabian Society, for access to various Labour and socialist ma terials; to the Rutgers University Research Council for grants in support of some of the research; and to Mrs. Edward Teifeld and Mrs. Boris Pritsky for the wearisome efforts of typing various versions of the manuscript. The responsibility for errors is, of course, mine. The book is dedicated to my wife Marilyn, who aided so greatly in its preparation, not least by a tactful and appropriate balance of patience and impatience.